Meningkatkan Hasil Belajar Pak dengan Model PBL Materi Aku Pribadi yang Unik Fase B Kelas IV SD RK ST Maria Pakkat - Rismaduma Marbun (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to determine the improvement of cognitive and affective learning outcomes in the dimensions of faith and devotion to God Almighty and Mutual Cooperation through the PBL model in students at SD RK ST MARIA PAKKAT. This type of research is classroom action research with research steps, namely planning, implementation, observation and reflection in each cycle. This study consists of two cycles. The place of research at SD RK ST MARIA PAKKAT. in grade IV students with the material I AM A UNIQUE PERSON. The time of the study was carried out in September 2024. The data collection technique used the Learning Outcome test and affective observation rubric. The data analysis technique used quantitative descriptive techniques. From the results of the study, there was an increase in cognitive learning outcomes by 20% in the Proficient criteria and 5% in the Proficient criteria. Affective Learning Outcomes using the PBL learning model have been proven to improve the affective learning outcomes of students at SD RK ST MARIA PAKKAT on the material I AM A UNIQUE PERSON. The results of the improvement can be seen from the number of students in cycle I, 75% of whom entered the Proficient criteria and in cycle II there was a significant change, namely 92% entered the Proficient criteria.